FERMENTASI TALAS BELITUNG (Xanthosoma sagittifolium (L.) Schott) DENGAN VARIASI RAGI DAN PENAMBAHAN NUTRISI DALAM - Mardiyah Mardiyah; Srikandi Srikandi; RTM Sutamihardja (JURNAL SAINS NATURAL, 2015)
Fermentation of Belitung Taro (Xanthosoma sagittifolium (L.) Schott) with variation of Yeast and Adding Nutrition to Produce Ethanol Plants that are potential to produce bioethanol are plants that have sugar or carbohydrate levels one of which is Belitung taro (Xanthosoma sagittifolium). This research aims to make bioethanol with simple fermentation process with variation on yeast type (bread yeast and tape yeast) and with the addition of nutrients (NPK fertilizer) to obtain maximum bioethanol content. This research was begun by making taro pulp with four treatments and each treatment repeated 3 times. The four treatments consist of taro belt with yeast bread, yeast bread and NPK, yeast tape, yeast tape and NPK. Observations were performed on days 2, 4, 6, 7, 14 which included observation of pH and ethanol content. In addition, proximate test is also done. The results showed that the highest ethanol content in the fermentation process with yeast yeast occurred on the 7th day of 3.64% while in the yeast tape the highest level occurred on the 4th day of 3.07%. Addition of NPK can not produce maximum ethanol content. For proximate test, the result showed that the content of ash is high enough that is 4.57% while for carbohydrate, protein, fat, coarse fiber, and moisture content obtained results equivalent to the literature.Keywords: Ethanol, Fermentation, Belitung Taro, Bioethanol ABSTRAKTumbuhan yang potensial untuk menghasilkan bioetanol adalah tanaman yang memiliki kadar gula atau karbohidrat salah satunya yaitu talas belitung (Xanthosoma sagittifolium). Penelitian ini bertujuan untuk membuat bioetanol dengan proses fermentasi sederhana dengan variasi pada jenis ragi (ragi roti dan ragi tape) serta dengan penambahan nutrisi (pupuk NPK) sehingga didapatkan kadar bioetanol yang maksimal. Diawali dengan membuat bubur talas belitung dengan empat perlakuan dan setiap perlakuan diulang 3 kali. Empat perlakuan terdiri atas talas belitung dengan ragi roti, ragi roti dan NPK, ragi tape, ragi tape dan NPK. Pengamatan dilakukan pada hari ke 2, 4, 6, 7, 14 yang meliputi pengamatan pH dan kadar etanol. Selain itu dilakukan juga uji proksimat. Hasil penelitian menunjukkan bahwa kadar etanol tertinggi pada proses fermentasi dengan ragi roti terjadi pada hari ke-7 yaitu 3,64% sedangkan pada ragi tape kadar tertinggi terjadi pada hari ke-4 yaitu 3,07%. Penambahan NPK tidak dapat menghasilkan kadar etanol yang maksimal. Untuk pengujian proksimat didapatkan kadar abu yang cukup tinggi yaitu 4,57% sedangkan untuk kadar karbohidrat, protein, lemak, serat kasar, dan kadar air didapatkan hasil yang setara dengan literatur.Kata Kunci : Etanol, Fermentasi, Talas Belitung, Bioetanol